The influence of Twitter on social support among university students - Ssemuddu, Imran; Wok, Saodah (2021)
Social media has become a large part of modern day lives, especially in the use of Twitter among young adults. As such, this study aims to analyze the relationships that Twitter usage, attitude, and social experience may have with social support among university students. The study is guided by social support theory, and it adopts a quantitative research design using the survey method with questionnaire as the research instrument for data collection. A total of 250 university students from International Islamic University Malaysia (IIUM) participated in the study. The findings of the study indicate that students do use Twitter for social support among them. The levels of Twitter usage, attitude, social experience, and social support were found to be high. The study also found significant relationships between Twitter usage, attitude, and social support. However, the results revealed that social experience in using Twitter was insignificant for social support. Thus, the social support theory used in this study is partially supported. Suggestions for future research are also provided.